Self-collection of samples as an additional approach to deliver testing services for sexually transmitted infections: a systematic review and meta-analysis - Ping Teresa Yeh; Caitlin E Kennedy; Manjulaa Narasimhan; Igor Toskin; Yasmin Ogale (BMJ Global Health)
Background Self-collection of samples for diagnostic testing offers the advantages of patient autonomy, confidentiality and convenience. Despite data showing their feasibility and accuracy, there is a need to better understand how to implement such interventions for sexually transmitted infections (STIs). To support WHO guidelines on self-care interventions, we conducted a systematic review to investigate whether self-collection of samples should be made available as an additional approach to deliver STI testing services.Methods Peer-reviewed studies were included if they compared individuals who self-collected samples for chlamydia, gonorrhoea, syphilis and/or trichomonas testing to individuals who had samples collected by clinicians on the following outcomes: uptake/frequency of STI testing, social harms/adverse events, positive yield (case finding), linkage to clinical assessment/treatment and reported sexual risk behaviour. We searched PubMed, CINAHL, LILACS and EMBASE for articles published through July 2018. Risk of bias was assessed using the Cochrane tool for randomised controlled trials (RCTs) and the Evidence Project tool for non-RCTs. Meta-analysis was conducted using random effects models to generate pooled estimates of relative risk (RR).Results Eleven studies, including five RCTs and six observational studies with a total of 202 745 participants, met inclusion criteria. Studies were conducted in Australia, Denmark and the USA. Meta-analysis found that programmes offering self-collection of samples increased overall uptake of STI testing services (RR: 2.941, 95% CI 1.188 to 7.281) and case finding (RR: 2.166, 95% CI 1.043 to 4.498). No studies reported measuring STI testing frequency, social harms/adverse events, linkage to care or sexual risk behaviour.Discussion While greater diversity in study designs, outcomes and settings would strengthen the evidence base, findings from this review suggest that self-collection of STI samples could be an effective additional strategy to increase STI testing uptake.Prospero registration number PROSPERO CRD42018114866.